2018
DOI: 10.1111/cea.13162
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylserine receptor P2Y10: A G protein‐coupled receptor that mediates eosinophil degranulation

Abstract: LysoPS provokes eosinophil degranulation through P2Y10. Therefore, P2Y10 is a potential therapeutic target to control eosinophil-associated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…EoL-1 cells were maintained at 1 × 10 6 /mL in Roswell Park Memorial Institute (RPMI) 1640 medium (Sigma-Aldrich, St. Louis, MO, United States) supplemented with 10% fetal bovine serum in 5% CO 2 at 37 • C and differentiated by adding 0.5 µM butyrate (Sigma-Aldrich, St. Louis, MO, United States) for 2 days. To examine the effects of TLR ligands on the differentiated EoL-1 cells, butyratetreated EoL-1 cells were stimulated with poly(I:C) (10 µM, InvivoGen, San Diego, CA, United States), LPS (1 ng/mL, Sigma-Aldrich, St. Louis, MO, United States), palmitic acid (250 mM, Sigma-Aldrich, St. Louis, MO, United States), or R848 (1 µg/mL, InvivoGen, San Diego, CA, United States) for 24 h. Human eosinophils were differentiated from CB CD34 + cells for 24 days as previously described in detail (Hwang et al, 2016(Hwang et al, , 2018.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…EoL-1 cells were maintained at 1 × 10 6 /mL in Roswell Park Memorial Institute (RPMI) 1640 medium (Sigma-Aldrich, St. Louis, MO, United States) supplemented with 10% fetal bovine serum in 5% CO 2 at 37 • C and differentiated by adding 0.5 µM butyrate (Sigma-Aldrich, St. Louis, MO, United States) for 2 days. To examine the effects of TLR ligands on the differentiated EoL-1 cells, butyratetreated EoL-1 cells were stimulated with poly(I:C) (10 µM, InvivoGen, San Diego, CA, United States), LPS (1 ng/mL, Sigma-Aldrich, St. Louis, MO, United States), palmitic acid (250 mM, Sigma-Aldrich, St. Louis, MO, United States), or R848 (1 µg/mL, InvivoGen, San Diego, CA, United States) for 24 h. Human eosinophils were differentiated from CB CD34 + cells for 24 days as previously described in detail (Hwang et al, 2016(Hwang et al, , 2018.…”
Section: Cell Culturementioning
confidence: 99%
“…We next checked expression levels of TLRs in EoL-1 cells and observed that transcripts of TLR3, TLR4, TLR7, TLR8, and TLR9 were significantly increased in dEoL-1 cells ( Figure 1A). Eosinophils arise from CD34 + hematopoietic stem cells (Rothenberg and Hogan, 2006), and we previously demonstrated that culturing CB CD34 + cells for 24 days with eosinophil lineage committed cytokines produces mature eosinophils (Hwang et al, 2016(Hwang et al, , 2018; Supplementary Figure S2). As shown in Figure 1B, we found apparent mRNA expression for TLR2, TLR4, TLR6, TLR8, and TLR9 in CB-derived eosinophils (FPKM > 1), and expression of TLR4 transcript was the highest compared to other TLRs (FPKM = 27.97 ± 1.67).…”
Section: Tlr Expression Is Induced In Differentiated Eol-1 Cells and mentioning
confidence: 99%
“…5 Our previous study demonstrated that when PB eosinophils were exposed to LysoPS at 10 μmol/L or less for four days, survival/apoptosis of LysoPS-treated eosinophils was not significantly different from those of untreated eosinophils. 28 However, further experiments showed that detectable amounts of LDH were released upon exposure to 10 μmol/L LysoPS for Figure 1Ai). The DNA filaments in EETs from LysoPS-stimulated eosinophils were preferentially projected toward neighboring cells, suggesting that cohesion of eosinophil DNA traps is contact-dependent.…”
Section: Lysops Induces Eosinophil Extracellular Trap Formationmentioning
confidence: 92%
“…Although LysoPS does not induce chemotaxis or affect cell survival/ apoptosis, eosinophils from patients with blood eosinophilia release detectable amounts of eosinophil cationic protein (ECP) in response to 10 μmol/L LysoPS. 28 Two other lysophospholipids affect eosinophil functions in addition to LysoPS. Lysophosphatidic acid induces eosinophil chemotaxis and upregulates adhesion molecules in a range of ~10 -5 -10 -3 M in a pertussis toxin (PTX)-dependent manner, 29 while lysoplatelet-activating factor (LysoPAF) triggers eosinophil degranulation at ~10 -6 M independently of PTX and is more potent than PAF.…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
See 1 more Smart Citation